Physicochemical quality evaluation of amoxicillin capsules produced in compounding pharmacies at Diadema, São Paulo, Brazil - Fúlvio Gabriel Corazza, Blanca Elena Ortega Markman, Paulo César Pires Rosa (Journal of Applied Pharmaceutical Science, 2015)
The evaluation of the physicochemical quality of amoxicillin (500 mg) capsules produced in Compounding Pharmacies at Diadema - SP - Brazil, was performed by comparing these capsules with reference, generic and similar drugs, through the dissolution, assay, average weight, water content analysis, all according to the pharmacopeial methodology. The compounded drug samples were acquired on 8 different Compounding Pharmacies of Diadema (M1, M2, M3, M4, M5, M6, M7, M8), and five (reference, generic and similar) drug samples (R, G1, G2, S1, S2) produced by distinct pharmaceutical industries were obtained from different Drugstores also at the same area. The samples were evaluated using the methodology proposed by the American and Brazilian Pharmacopoeia. All samples were approved in the dissolution and water content assay. Only samples R and S1 were approved assay of dose. Samples M3, M4 and S1 were disapproved in the average weight assay. The non-fulfillment of the Brazilian Good Manufacturing Practices recommended procedures for industries and compounding pharmacies show the need for improvements in the overall drug quality control manufacturing process of finished products in consonance with the actual health legislation, guaranteeing access to safe, effective medicines, control of bacterial resistance and rational use of antibiotics.
Keywords: Amoxicillin. Capsules. Quality Control. Compounding Pharmacies.